Heterogeneous myocyte enhancer factor-2 (Mef2) activation in myocytes predicts focal scarring in hypertrophic cardiomyopathy - Konno, Tetsuo (National Academy of Sciences, 2010)
Unknown molecular responses to sarcomere protein gene mutations account for pathologic remodeling in hypertrophic cardiomyopathy (HCM), producing myocyte growth and increased cardiac fibrosis. To determine if hypertrophic signals activated myocyte enhancer factor-2 (Mef2), we studied mice carrying the HCM mutation, myosin heavy-chain Arg403Gln, (MHC(403/+)) and an Mef2-dependent β-galactosidase reporter transgene. In young, prehypertrophic MHC(403/+) mice the reporter was not activated. In hypertrophic hearts, activation of the Mef2-dependent reporter was remarkably heterogeneous and was observed consistently in myocytes that bordered fibrotic foci with necrotic cells, MHC(403/+) myocytes with Mef2-dependent reporter activation reexpressed the fetal myosin isoform (βMHC), a molecular marker of hypertrophy, although MHC(403/+) myocytes with or without βMHC expression were comparably enlarged over WT myocytes. To consider Mef2 roles in severe HCM, we studied homozygous MHC(403/403) mice, which have accelerated remodeling, widespread myocyte necrosis, and neonatal lethality. Levels of phosphorylated class II histone deacetylases that activate Mef2 were substantially increased in MHC(403/403) hearts, but Mef2-dependent reporter activation was patchy. Sequential analyses showed myocytes increased Mef2-dependent reporter activity before death. Our data dissociate myocyte hypertrophy, a consistent response in HCM, from heterogeneous Mef2 activation and reexpression of a fetal gene program. The temporal and spatial relationship of Mef2-dependent gene activation with myocyte necrosis and fibrosis in MHC(403/+) and MHC(403/403) hearts defines Mef2 activation as a molecular signature of stressed HCM myocytes that are poised to die.